Women, Peace, and Security Agenda in Africa - Chigudu, Daniel (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The complex opportunities and challenges of the Women, Peace and Security (WPS) Agenda articulated in the UN Security Council Resolution 1325 of 2000, and other successive resolutions, subject themselves to the proverbial interpretation of either a cup half-empty or a cup half-full. The WPS is a progressive agenda for gender programmes in Africa. The downside is that the WPS agenda appears not known beyond policy and activist circles in the continent. This study sought to interrogate the progress made by the WPS agenda in Africa since the UNSCR 1325 was adopted using secondary research and content analysis (CA) of current literature. It was revealed that despite some challenges faced the gender perspective is not deficient in peacekeeping operations (PKOs) except in peace agreements, but that gender 1325 commitments are mirrored in the mandates of PKOs. The African Union-United Hybrid Operation in Darfur (UNAMID), showed the least WPS agenda consideration but the United Nations Multidimensional Integrated Stabilisation Mission in the Central African Republic (MINUSCA) significantly reflected this. For the rest of Africa, it remains unclear if the agenda is stagnating or going forward. There is a host of structural challenges rooted in masculinity issues and patriarchal mind-sets among others.